The lost legions of Fromelles : the true story of the most dramatic battle in Australia's history - Barton, Peter, 1955- (Allen & Unwin, 2014)
Peter Barton has written an authoritative and revelatory book on Fromelles. He describes its long and surprising genesis, and offers an unexpected account of the fighting. He investigates the interrogation of Anglo-Australian prisoners and the results of shrewd German propaganda techniques, and he explores the circumstances surrounding the 'missing' Pheasant Wood graves. He also brings new perspectives to the writing of Charles Bean. This compelling an illuminating history dispels many a myth surrounding of the bloodiest battlefields of the Great War.